3+4x=5-6x

Simple and best practice solution for 3+4x=5-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+4x=5-6x equation:


Simplifying
3 + 4x = 5 + -6x

Solving
3 + 4x = 5 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
3 + 4x + 6x = 5 + -6x + 6x

Combine like terms: 4x + 6x = 10x
3 + 10x = 5 + -6x + 6x

Combine like terms: -6x + 6x = 0
3 + 10x = 5 + 0
3 + 10x = 5

Add '-3' to each side of the equation.
3 + -3 + 10x = 5 + -3

Combine like terms: 3 + -3 = 0
0 + 10x = 5 + -3
10x = 5 + -3

Combine like terms: 5 + -3 = 2
10x = 2

Divide each side by '10'.
x = 0.2

Simplifying
x = 0.2

See similar equations:

| 19=30-x | | 2(b+3)-(9+b)=-6 | | 1.8=0.6y | | 5(5k+2)-2(4k-3)= | | 3(k-5)=5(k-9) | | 4x-26=x+31 | | 66c=u-8 | | 4n+3=6n-5 | | 3a^2-6a= | | 6=13-x | | 7x+5=12x-5 | | 7x+8-36x-9=4x+2 | | 7n-28=54 | | -6x+13=-x+8 | | 2x-12=7x-2 | | 7(4x-3)-4x=-16 | | 6q+20=19 | | -3x-15=-6 | | 3x+8+2x-3=75 | | -2(-07m+9)=4(m-7) | | 127.82=2.35h+73.77 | | 3r-2=5(r+2) | | 2(-7m+9)=4(m-7) | | 3(2x-4)=0 | | 7y+3y=9y+9 | | 12x+34=10x+200 | | 8x-3=2x+27 | | 18w-2=10-14 | | 5x+22=x+2 | | 7(-3x+5)+8=148 | | 7t-t-8=5t-4 | | 2w+6x-14y+5w+9x+8y= |

Equations solver categories